Plasma jet printing induced high-capacity graphite anodes for sustainable recycling of lithium-ion batteries. (15th October 2022) - Bhar, Madhushri; Dey, Avishek; Ghosh, Sourav; van Spronsen, Matthijs A.; Selvaraj, Vimalnath; Kaliprasad, Y.; Krishnamurthy, Satheesh; Martha, Surendra K.
Abstract: Graphite is an integral part of lithium-ion batteries (LIBs). However, due to limited resources and high production cost, producing battery grade graphite to meet the increasing demands for energy storage devices is becoming a challenge. One viable approach is to recycle the spent graphite anodes from end-of-life LIBs. Importantly, recycling of spent lithium-ion batteries (LIBs) is off utmost importance to address the global challenge of electronic waste management. Herein, we present an environmentally friendly technique of graphite recycling from spent LIB by water leaching, followed by atmospheric plasma jet printing. The major advantage of this method is that it does not require any binders or conductive diluents. Plasma-printed recycled graphite showed a significantly enhanced specific capacity of 402 mAh g −1 at 500 mA g −1 at the end of the 1000th charge-discharge cycle, in comparison to water-washed recycled graphite (112 mAh g −1 ) and a 23.35 times faster diffusivity of Li + . A detailed experimental investigation revealed that the plasma activation of the graphitic structure resulted in the improved reversible Li + storage. This work provides a new perspective on the recycling strategy of graphite anodes using in situ plasma functionalization, a significant step towards the sustainable future of LIBs. Graphical abstract: Here, we demonstrate an eco-friendly method to recycle graphite from spent Lithium-ion batteries (LIBs). High-capacity anodes are prepared by plasma jet printing of extracted graphite without the use of conventional additives. This study paves the way towards sustainable recycling of spent LIB anodes to be reused as high-performance anode material for LIBs using plasma printing technology. Image 1